Cyclosporin A plus prednisone treatment of steroid-sensitive frequently relapsing nephrotic syndrome in children - Aksu, Nejat; Türker, Meral; Erdoğan, Hakan; Özinel, Sema; Kansoy, Savaş (The Turkish Journal of Pediatrics, 1999)
Recently, there have been numerous reports on the use of cyclosporin A (CyA) in children with nephrotic syndrome (NS). In this prospective study, we wanted to evaluate the efficacy of CyA together with prednisone therapy in children with steroid-sensitive frequently relapsing NS. A total of 11 children (7 boys, 4 girls) with steroid-sensitive NS were included in this study. The patients ranged in age from 3.5 to 15 years (average 8.45 ± 4.26 years). Renal biopsy showed minimal change disease in five, mesangial proliferation in four, focal glomerulosclerosis in one and membranous glomerulonephritis in one. The NS had lasted from 13 to 113 months (average 50.27 ± 38.60 months). The number of relapses varied from three to 10 episodes with an average of 5.9 ± 3.3 episodes. Patients received 5 mg/kg CyA daily in two divided doses for five months and prednisone for a total of eight weeks (30 mg/m² daily for 4 weeks followed by 30 mg/m² on alternate days for 4 weeks). After the completion of the treatment protocol, no therapy was given unless a relapse was observed. Mean follow-up period was 14.9 ± 5.99 months with a range from six to 26 months. Before this combined treatment, there was a mean relapse rate of 0.144 ± 0.05 relapses month with a range from 0.088 to 0.238. After discontinuation of therapy, the relapse rate dropped to a mean of 0.0179 ± 0.031 with a range of 0 to 0.083. In conclusion, it would appear that a combination of CyA and prednisone is effective, sustaining the remission in steroid-sensitive NS. Corticosteroids in combination with CyA may be a better approach than conventional steroid treatment in such patients.